Nurse Performance and Communication Skills: Psychological Mediation and Compensation Moderation within a Conditional Process Model - Mubyl, Mutiarini (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
This study examines the indirect relationship between nurses’ communication skills and job performance, testing a conditional process with psychological mediators and compensation as moderator. Its academic contribution clarifies that psychological pathways, rather than extrinsic rewards, are the primary mechanism translating communicative competence into performance in healthcare organizations. A quantitative survey of 148 nurses at a mental hospital in South Sulawesi, Indonesia, operationalizes work satisfaction and subjective wellbeing as mediators. Results indicate communication skills significantly enhance satisfaction and wellbeing; satisfaction emerges as the stronger mediator of performance. By contrast, neither the direct effect of communication on performance nor the moderating role of compensation reaches statistical significance. Managers should prioritize communication training and interventions that cultivate satisfaction and wellbeing, which outperform compensation tweaks in lifting nurse performance.